Kompetensi Pedagogi Dalam Peningkatan Mutu Pendidikan Di SMPN 6 Nekamese - Widyanti, Lidyasih; Tari, Ezra (Sekolah Tinggi Teologi Real Batam, 2024)
Some teachers face difficulties in managing classrooms, especially when dealing with students who exhibit challenging behavior or have diverse abilities. The curriculum often changes in line with government policies, and some teachers struggle to adapt quickly, causing the material taught to not always align with the demands of the latest curriculum. This study aims to examine the pedagogical competence of teachers in improving the quality of education within the framework of Merdeka Belajar at SMPN 6 Nekamese. The method used is qualitative research at SMP Negeri 6 Nekamese, Kupang Regency, with the main informants being teachers who actively implement the Merdeka Belajar concept. The